Manajemen RKAS dan Efektivitas Program Sekolah: Studi di SDN Babatan 1 Surabaya - Rahma, Sofia Annisa; Vitacheria, Firsty Gracia; Putri, Sabrina Imelda; Rahayu, Esti Adristi Dian; Widiyanah, Ima (Lembaga Yasin AlSys, 2026)
Although the management of the School Activity and Budget Plan (RKAS) has received attention in various previous studies, research specifically discussing the effectiveness of RKAS management in supporting school programs at the elementary school level remains limited. This study aims to analyze RKAS management in improving the effectiveness of school programs at SDN Babatan 1 Surabaya. This study used a qualitative approach with a case study design. The research informants included the principal, school treasurer, and teachers involved in the preparation and implementation of RKAS. Data were collected through interviews, observation, and documentation, and were then analyzed using an interactive data analysis model comprising data reduction, data display, and conclusion drawing. The results showed that RKAS management at SDN Babatan 1 Surabaya was implemented through the stages of planning, organizing, implementation, and evaluation in a participatory manner by involving various school elements. The implementation of RKAS was considered fairly effective in supporting the implementation of school programs, although it still faced constraints in the form of budget limitations and the need to adjust program priorities. These findings contribute to the development of studies on educational financing management and expand understanding of the importance of transparent, accountable, and participatory RKAS management in improving the quality of school programs. The conclusion of this study affirms that planned and participatory RKAS management plays an important role in supporting the effectiveness of school program implementation. The implications of this study include practical contributions for schools in strengthening effective and efficient financial governance, while also opening opportunities for further research on the digitalization of RKAS management in elementary education institutions.